Mobilizing East Asia online: MEAO (BrillOnline Primary Sources, 2018)
Mobilizing East Asia offers a carefully selected collection of extremely rare, many times even unique English-language newspapers,magazines and pamphlets published inside Asia, following the descentinto war in East and South-East Asia from the turn of the twentiethcentury to the 1950s.This exciting collection of newspapers and illustrated magazines, oftenin colour, is now available online for the first time, exclusively fromBrill. The Collection offers access to unique primary source materialwhich can be used to pursue research topics in modern history, Asianstudies, politics and war studies. Features and Benefits:-- English-language newspapers and magazines published in East Asia- Approx. 100,000 pages of over 1,200 print items- All content fully searchable- Reproduced in 300 dpi full colour- Sourced from extremely rare, often even unique originals